L’andamento nel tempo delle disparità scolastiche in Italia e il rebus delle classi medie sovrascolarizzate - Barone, Carlo (SocietàMutamentoPolitica, 2013)
This article presents empirical evidence on trends over time in educational inequalities in Italy and focuses on the school attainment of middle classes. The analyses are based on a cumulative dataset that covers with large numbers the cohorts schooled over the past century, including the most recent cohorts. Class of origin is defined according to the EGP schema, rather than the traditional Cobalti-Schizzerotto schema. Results point to a long-term trend of declining inequality in education that has however slowed down in recent cohorts.